Integrating ecosystem services supply and demand on the Qinghai-Tibetan Plateau using scarcity value assessment. (March 2023) - Zhang, Shidong; Wu, Tong; Guo, Luo; Zou, Huiting; Shi, Yu
Highlights: The scarcity value of ecosystem services (ES) was evaluated on the Qinghai-Tibetan Plateau (QTP) by linking supply and demand. The spatial heterogeneities of ES scarcity value and its response to urbanization were identified. The surging demand for public-good ES contributed to a significant increase in scarcity value. There was a spatial consistency between ES scarcity value and economic conditions during urbanization. Abstract: As a result of the land degradation it causes, rapid urbanization can severely impact the form and function of the natural environment. Because of the limited availability of natural capital and the ecosystem services they provide in many regions, fluctuations in supply and demand should rigorously considered in decision-making. The Qinghai-Tibetan Plateau (QTP) is a globally-important ecoregion that generates significant ecosystem services value. Focusing on the QTP, we calculated the value change in the supply of ecosystem services using a coefficient table and the change in demand based on population, GDP, and income elasticity. The impact of supply and demand on the scarcity value of ecosystem services (ESSV) was then compared across four representative scenarios. The results showed that the ESSV on the QTP rose considerably between 1990 and 2020, particularly between 2000 and 2010. Between 1990 and 2020, the public-goods services grew faster than private-goods services. The most important element impacting the ESSV was demand-driven scarcity . The level of urbanization gradually increased during 1990–2020, with a consistent distribution of high ESSV and high urbanization across the region. High-High types and Low-Low types had a significant aggregation effect, located primarily in the north and west of the QTP, respectively. The Low-High type was scattered along with the Low-Low type, indicating fragile ecological conditions that merit greater protection from land degradation. The degree of coupling reveals an increasing degree of synergy between ESSV and urbanization on the QTP, indicating potential for more synergistic development.